Tiempo de recuperación post anestésica asociado al uso de músicoterapia durante la anestesia general balanceada en pacientes sometidos a colecistectomía laparoscópica en el Hospital Belén de Trujillo - Sánchez Rojas, José Carlos (2020)
Introduction: The post anesthetic recovery must be fast, safe and with a high degree of satisfaction. The use of music therapy has the potential to reduce pain and anxiety. However, no conclusive results have been found about the benefits of music during general anesthesia. Objective: To demonstrate if there is a relationship between post anesthetic recovery time and the use of music therapy during General Balanced Anesthesia. Method: Cohort-type observational study where post-anesthetic recovery time was evaluated according to the Aldrete score in 90 ASA I / II patients, aged 18-80, of both sexes, scheduled for Laparoscopic Cholecystectomy under Balanced General Anesthesia in the Hospital Belen de Trujillo from January-May 2018, divided into two groups (n = 45), group A exposed to music therapy and group B unexposed. Results: Recovery time at 5 minutes (53.3% vs. 20%), recovery time at 10 minutes (37,8% vs. 71.1%), recovery time at 15 minutes (8.9% vs. 8.9%) , group A vs group B, respectively. Conclusion: If there is a relationship between the use of music therapy during general anesthesia and the post anesthetic recovery time.